2016
DOI: 10.1073/pnas.1601135113
|View full text |Cite
|
Sign up to set email alerts
|

What grades and achievement tests measure

Abstract: Intelligence quotient (IQ), grades, and scores on achievement tests are widely used as measures of cognition, but the correlations among them are far from perfect. This paper uses a variety of datasets to show that personality and IQ predict grades and scores on achievement tests. Personality is relatively more important in predicting grades than scores on achievement tests. IQ is relatively more important in predicting scores on achievement tests. Personality is generally more predictive than IQ on a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
170
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(197 citation statements)
references
References 31 publications
(12 reference statements)
9
170
1
1
Order By: Relevance
“…Grades are highly loaded on non-cognitive measures and, properly standardized, provide good measures of social and emotional skills. 36 Borghans et al (2016) show that high school grades predict later life achievement in a range of domains. 37 These authors compare their predictive validity with those of standard achievement tests and find them much more predictive.…”
Section: Measurementmentioning
confidence: 99%
“…Grades are highly loaded on non-cognitive measures and, properly standardized, provide good measures of social and emotional skills. 36 Borghans et al (2016) show that high school grades predict later life achievement in a range of domains. 37 These authors compare their predictive validity with those of standard achievement tests and find them much more predictive.…”
Section: Measurementmentioning
confidence: 99%
“…More recent evidence shows that a range of traits that are often summarized as “non‐cognitive” or “socio‐emotional” skills play an equally important role in shaping students' everyday learning behaviors and their academic performance (De Feyter, Caers, Vigna, & Berings, ; Poropat, ; Spengler, Brunner, Martin, & Lüdtke, ). Besides motivational constructs such as task values or academic self‐concepts (Eccles & Roeser, ; Marsh, ; Marsh & O'Mara, ), the Big Five personality traits have emerged as potent predictors of academic performance at school (Borghans, Golsteyn, Heckman, & Humphries, ; Poropat, ; Vedel & Poropat, ) and university (McAbee & Oswald, ; Richardson, Abraham, & Bond, ; Vedel, ).…”
Section: Introductionmentioning
confidence: 99%
“…The associations of cognitive ability and personality with academic performance vary somewhat across different measures of academic performance. Whereas cognitive ability has emerged as the best predictor of standardized achievement test scores, personality traits are typically more strongly related to school grades (Borghans et al, ; Lechner et al, ; Spinath et al, ). One reason for this is that school grades (in contrast to objective tests) contain teachers' subjective evaluations of students' learning and classroom behavior (Spengler, Lüdtke, Martin, & Brunner, ).…”
Section: Introductionmentioning
confidence: 99%
“…The predictive power of personality tests can be higher or lower than that of IQ depending on the measures used (6)(7)(8). Although most studies have reported contemporaneous correlations, there is evidence that traits measured at adolescence predict educational attainment and adult income (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%